Measuring the Pharmacokinetic Properties of Drugs with a Novel Surgical Rat Model. (4th May 2017) - Christakis, Ioannis; Scott, Rebecca; Minnion, James; Cuenco, Joyceline; Tan, Tricia; Palazzo, Fausto; Bloom, Stephen
ABSTRACT: Purpose/aim of the study : The pharmacokinetic (PK) parameters in animal models can help optimize novel candidate drugs prior to human trials. However, due to the complexity of pharmacokinetic experiments, their use is limited in academia. We present a novel surgical rat model for investigation of pharmacokinetic parameters and its use in an anti-obesity drug development program. Materials and methods : The model uses anesthetized male Wistar rats, a jugular, a femoral catheter, and an insulin pump for peptide infusion. The following pharmacokinetic parameters were measured: metabolic clearance rate (MCR), half-life, and volume of distribution (Vd). Glucagon-like peptide 1 (GLP-1), glucagon (GCG), and exendin-4 (Ex-4) were used to validate the model. The pharmacokinetic parameters of anti-obesity drug candidates X1, X2, and X3 were measured. Results : GLP-1 had a significantly higher MCR (83.9 ± 14.1 mL/min/kg) compared to GCG (40.7 ± 14.3 mL/min/kg) and Ex-4 (10.1 ± 2.5 mL/min/kg) ( p < .01 and p < .001 respectively). Ex-4 had a statistically significant longer half-life (35.1 ± 7.4 min) compared to both GCG (3.2 ± 1.7 min) and GLP-1 (1.2 ± 0.4 min) ( p < .01 for both GCG and GLP-1). Ex-4 had a statistically significant higher volume of distribution (429.7 ± 164.9 mL/kg) compared to both GCG (146.8 ± 49.6 mL/kg) and GLP-1 (149.7 ± 53.5 mL/kg) ( p < .01 for both GCG and GLP-1). Peptide X3 had a statistically significant longer half-life (21.3 ± 3.5 min) compared to both X1 (3.9 ± 0.4 min) and X2 (16.1 ± 2.8 min) ( p < .001 for both X1 and X2). Conclusions : We present an affordable and easily accessible platform for the measurement of PK parameters of peptides. This novel surgical rat model produces consistent and reproducible results while minimizing animal use.